Jerapan Isotermal Fosfat Pada Tanah Ultisol - Muhammad Asnandi; Fadly Hairannoor Yusran; Muhammad Syarbini (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2023)
The distribution area of mineral soil in Indonesia reaches 148 million ha. The acid mineral soil in South Kalimantan for Ultisol reaches 886.186 ha. Ultisols have low fertility and P availability. The low availability of P in the soil is caused by P being absorbed. Isothermal absorption is very useful for measuring P adsorption in the soil due to strong P fixation by Fe and Al in Ultisol soils. Many researchers have suggested determining the amount of P required to reach an optimum level for maximum crop yield to quantitatively describe isothermal adsorption, the most popular of which are Langmuir, Freundlich, and the Brunauer-Emmett-Teller (BET) equations. The purpose of this study was to determine the isothermal adsorption limit of P and describe quantitatively the isothermal adsorption in Ultisols in Banjarbaru City using the Langmuir, Freundlich, and BET equations. From the research results, it can be concluded that P adsorption on Ultisols in Gunung Kupang Village, Cempaka District, Banjarbaru City follows the BET Equation. The high and low P adsorption indicated the availability of P. In other words, the fixation activity of acid mineral soils could result in a smaller amount of available P for plants.